2015
DOI: 10.1523/jneurosci.4349-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Methionine Metabolism and Histone H3 Trimethylation Are Linked to Mitochondrial Defects in Multiple Sclerosis

Abstract: Mitochondrial changes, including decreased expression of electron transport chain subunit genes and impaired energetic, have been reported in multiple sclerosis (MS), but the mechanisms involved in these changes are not clear. To determine whether epigenetic mechanisms are involved, we measured the concentrations of methionine metabolites by liquid chromatography tandem mass spectrometry, histone H3 methylation patterns, and markers of mitochondrial respiration in gray matter from postmortem MS and control cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 52 publications
10
50
0
Order By: Relevance
“…Neurons with longer projections require increased ATP to maintain ion homeostasis and conduction of nerve impulses over long distances. Our data show that Hbb overexpression in SH-SY5Y neuroblastoma cells increased H3K4me3, a histone mark that is present in actively transcribed regions of chromatin and regulates expression of oxidative phosphorylation genes (Singhal et al 2015). A role for hemoglobin in mitochondrial respiration is supported by a study by Biagoli et al (2009) which suggested that alterations in hemoglobin expression affect cellular energetics, since dopaminergic cell lines over expressing α- and β-globin subunits exhibited changes in oxygen homeostasis and alterations in the expression of mitochondrial genes.…”
Section: Discussionmentioning
confidence: 85%
“…Neurons with longer projections require increased ATP to maintain ion homeostasis and conduction of nerve impulses over long distances. Our data show that Hbb overexpression in SH-SY5Y neuroblastoma cells increased H3K4me3, a histone mark that is present in actively transcribed regions of chromatin and regulates expression of oxidative phosphorylation genes (Singhal et al 2015). A role for hemoglobin in mitochondrial respiration is supported by a study by Biagoli et al (2009) which suggested that alterations in hemoglobin expression affect cellular energetics, since dopaminergic cell lines over expressing α- and β-globin subunits exhibited changes in oxygen homeostasis and alterations in the expression of mitochondrial genes.…”
Section: Discussionmentioning
confidence: 85%
“…Chromatin immunoprecipitation findings showed that betaine regulates metabolic genes in SH-SY5Y neuroblastoma cells. These data suggest that altered methionine metabolism may be tied to changes in neuronal energetics in multiple sclerosis cortex (Singhal et al, 2015).…”
Section: Epigenetics and Other Organ (Non-cardiac) Complications In Omentioning
confidence: 78%
“…This is evident by overt epigenetic modifications in cardiovascular anomalies including coronary heart disease, hypertension, peripheral vascular disease and stroke in the presence of major pro-epigenetic cardiovascular risk factors such as aging, high fat/caloric intake, exercise, drinking and tobacco abuse (Whayne, 2015). In addition, prevalence of cardiovascular diseases in adulthood is tightly controlled by early developmental factors such as gene imprinting, amniotic sac development, maternal and fetal nutritional status, among others (Horvath et al, 2014;Singhal et al, 2015;Thornburg, 2015). Through these epigenetic modifications, there may be infinite developmental cardiovascular benefit/harm for the fetus and newborn later on in adult life health status.…”
Section: Epigenetics Versus Genetics In the Regulation Of Heart Homeomentioning
confidence: 99%
“…Here, we show that mesenchymal GSCs preferentially activate 2 distinctive features ─ DNA hypomethylation and NAD + utilization ─ due to a switch in NAM metabolism regulated by high levels of NNMT and NAMPT (Supplemental Figure 2B). To date, functional contributions of NNMT to diet-induced obesity, insulin resistance, glucose, lipid, and cholesterol metabolism have been delineated (63,64). However, the oncogenic mechanisms of NNMT are poorly understood, despite high expression levels in many cancers, including GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Although N-methylation of histones is closely associated with functional changes of chromatin and, thus, is involved in cell biology (63,66), N-methylation of metabolites may serve as a point of fragility for tumor cells due to simultaneous effects on both metabolism and epigenetic modifications, as demonstrated by efficacy of NAMPT inhibitors in IDH1 mutant or MYC-amplified gliomas (67, 68). Further, NAMPT may regulate GBM sphere-forming cells through regulation of the inhibitor of differentiation (ID) pathway (69).…”
Section: Discussionmentioning
confidence: 99%